(untitled) (Journal of Computational Mathematics, 1998)
Some essential estimates, especially the so-called extension theorems, are established in this paper, for the nonconforming finite elements with their continuity at the vertices or the edge midpoints of the elements of the quasi-uniform mesh. As in the conforming discrete cases, these estimates play key roles in the theoretical analysis of the nonoverlap domain decomposition methods for the solving of second order self-adjoint elliptic problems discretized by the nonconforming finite element methods.